Bilayer and clickable electrospun membrane from tailored polyurethanes: A versatile platform for easy surface functionalization - Stefano Torresi; Unai Montejo; Ana Alonso-Varona; Nagore Gabilondo; Arantxa Eceiza (Journal of Science: Advanced Materials and Devices)
Two biobased linear polyurethanes were synthesized and electrospun to produce a final bilayer nanofibrous membrane. On one side, a thiol-containing composition, PU-SH, was used, while on the other side, a non-functionalized polyurethane, PU-PD, was employed. The bilayer membrane was conceived to be easily functionalized in water, taking advantage of the high reactivity of thiols. The accessibility and reactivity of the PU-SH layer were corroborated by labeling it with a maleimide-functionalized fluorescent molecule through a thiol-maleimide click reaction. Furthermore, considering the high hydrophobicity and the mechanical strength of PU-PD and the possible functionalization of the PU-SH layer with Ag nanoparticles (AgNPs), preliminary biocompatibility and antimicrobial studies were conducted for its application as wound dressing. The work demonstrated that accurate control of the polymeric backbone chemistry led to customizable membranes by the rapid, green, and homogeneous post-functionalization of the nanofibers with surface clickable groups.